3D-Printing Assisted SF-SA Based MgP Hybrid Hydrogel Scaffold for Bone Tissue Engineering - Mao, Qiuyi; Zhu, Bowen; Zhuang, Hai; Bu, Shoushan (Frontiers in Materials, 2022)
A new prototype of hybrid silk fibroin and sodium alginate (SF-SA) based osteogenic hydrogel scaffold with a concentration of 2.5% magnesium phosphate (MgP) based gel was prepared with the assistance of an extrusion-based three-dimensional (3D) printing machine in this study. To determine the optimum ratio of MgP based gel in the hydrogel, a series of physical and biochemical experiments were performed to determine the proper concentration of MgP in two-dimensional hydrogel films, as well as the cell compatibility with these materials in sequence. The SF-SA hydrogel with 2.5wt% magnesium phosphate (SF-SA/Mg) stood out and then was used to fabricate 3D hydrogel scaffolds according to the consequences of the experiments, with SF-SA hydrogel as a control. Then the morphology and osteogenic activity of the scaffolds were further characterized by field emission scanning electron microscope (SEM), calcium mineralization staining and reverse transcription-polymerase chain reaction(rt-PCR). The SF-SA/MgP hydrogel scaffold promoted the adhesion of rat mesenchymal stem cells with higher degrees of efficiency under dynamic culture conditions. After co-culturing in osteogenic differentiation medium, cells seeded on SF-SA/MgP hydrogel scaffold were shown to have better performance on osteogenesis in the early stage than the control group. This work illustrates that the 3D structures of hybrid SF-SA/MgP hydrogel are promising headstones for osteogenic tissue engineering.